Are carbonate barrier islands mobile?: Insights from a mid to late-Holocene system, Al Ruwais, northern Qatar - Rivers, John; Engel, Max; Dalrymple, Robert; Yousif, Ruqaiya; Strohmenger, Christian J.; Al-Shaikh, Ismail (Sedimentology, 2020)
Barrier islands are important landforms in many coastal systems around the globe. Studies of modern barrier island systems are mostly limited to those of siliciclastic realms, where the islands are recognized as mobile features that form on transgressive coastlines and migrate landward as sea-level rises. Barrier islands of the ‘Great Pearl Bank’ along the United Arab Emirates coast are the best-known carbonate examples. These Holocene islands, however, are interpreted to be anchored by older deposits and immobile. The mid-Holocene to late-Holocene depositional system at Al Ruwais, northern Qatar, provides an example of a mobile carbonate barrier island system, perhaps more similar to siliciclastic equivalents. Sedimentological and petrographic analyses, as well as 14C-dating of shells and biogenic remains from vibracored sediments and surface deposits, show that after 7000 years ago a barrier system with a narrow back-barrier lagoon formed along what is now an exposed coastal zone, while, contemporaneously, a laterally-extensive coral reef was forming immediately offshore. After 1400 years ago the barrier system was forced to step ca 3 km seaward in response to a sea-level fall of less than 2 m, where it re-established itself directly on the mid-Holocene reef. Since that time, the barrier has retreated landward as much as 1000 m to its current position, exposing previously-deposited back-barrier lagoonal sediment at the open-coast shoreline. In modern neritic warm-water carbonate settings mobile barrier island systems are rare. Their construction and migration may be inhibited by reef formation, early cementation, and the relative inefficiency of sourcing beach sediments from open carbonate shelves. Carbonate barrier island systems likely formed more commonly during geological periods when ramps and unrimmed shelves predominated and in calcite seas, when meteoric cementation was minimized as a result of initial calcitic allochem mineralogy. As with their siliciclastic analogues, however, recognition of the influence of these transient landforms in the rock record is challenging.
Online veröffentlicht: 7. August 2019
Gesehen am 29.10.2025